Khulu’ in Islamic Law: Concept, Procedure, and Its Legal Implications in the Family Law System - Ade Sultan Muhammad; R. Fahmi Natigor Daulay (Fox Justi : Jurnal Ilmu Hukum, 2026)
Khulu’ is a form of divorce in Islamic law that grants the wife the right to terminate a marriage by providing compensation (iwadh) to the husband. This concept reflects a legal mechanism that not only emphasizes the husband’s right to divorce (talak), but also ensures fairness and protection for women within marital relationships. This study aims to analyze the concept, legal basis, procedures, and legal consequences of khulu’ in Islamic law, as well as its relevance within the Indonesian family law system. The research employs a normative method with juridical and theological approaches, using primary sources such as the Qur’an and hadith, supported by classical fiqh literature and statutory regulations. The results indicate that khulu’ has strong normative legitimacy in Islam, with procedures based on mutual agreement between spouses and, in modern contexts, involving judicial institutions to ensure legal certainty. Legally, khulu’ results in the dissolution of marriage, changes in the rights and obligations of spouses, and adjustments in family rights, including maintenance, waiting period (iddah), child custody, and inheritance. In Indonesia, the concept of khulu’ is substantively accommodated through cerai gugat in Religious Courts, reflecting a transformation from classical Islamic jurisprudence to national legal practice. This study concludes that khulu’ is an essential legal instrument in promoting justice and balance within marriage, highlighting the importance of a comprehensive understanding of its concept and application in contemporary Islamic family law.